The atheist's way : living well without gods - Maisel, Eric, 1947- (Novato, Calif. : New World Library, 2009)
Psychotherapeut en filosoof Eric Maisel maakt in dit boek duidelijk dat we helemaal geen nood hebben aan religie of een God: we kunnen zelf betekenis geven aan ons leven en hebben geen godsdienst of Goden nodig.
Introduction: We embrace atheism (for many reasons)We have our traditions (did you know that?) -- We leave our churches (if we formerly believed) -- We make our own meaning (what a remarkable idea!) -- We invest meaning (another curious idea!) -- We nominate ourselves (as the heroes of our own stories) -- We get blue sometimes (who doesn't?) -- We deal with meaninglessness (yes, by making meaning) -- We choose our meanings (or do they choose us?) -- We make idiosyncratic meaning choices (as is our right and obligation) -- We maintain meaning (daily and over the long haul) -- We make our ethics (as active moral philosophers) -- We stand firm (even while consternated) -- Conclusion: We find life amazing (exactly as it is).
Includes bibliographical references and index
Keywords: Atheism; Conduct of life